Toward inclusivity through fashion: a qualitative exploration of the clothing consumption experiences of physically disabled men in South Korea - Sunwoo Kim; Hyungjin Son; Songmee Kim; Yeojin Lee; Yuri Lee (Fashion and Textiles)
Abstract This research addresses the need for inclusive innovation and research in the disability-inclusive fashion domain. We conducted a qualitative study to understand the barriers that male consumers with physical disabilities face in their clothing consumption experiences by applying grounded theory. To gain a comprehensive understanding of these barriers, we explored sociopsychological and fashion consumption-related factors alongside conventional functional considerations that influence their formation. Additionally, we suggested potential solutions to mitigate these barriers. Data for this exploratory qualitative study were collected through in-depth interviews with nine disabled male participants and four caregivers, combined with participatory observation, which was instrumental in building a strong rapport between the interview participants and the researcher. The findings suggest three dimensions of the barriers—functional, sociopsychological, and fashion consumption—and underscore the importance of sociopsychological influences in shaping their clothing consumption experiences. Furthermore, we emphasize the need for a universal fashion market that embraces both disabled and non-disabled consumers regardless of their physical attributes. To achieve this new direction in the fashion domain, it is necessary to leverage fashion industry advancements, such as mass customization with cutting-edge technologies, to address these multifaceted challenges. The research outcomes contribute to the advancement of disability-inclusive fashion and aim to enhance the overall well-being of individuals with disabilities. The research outcomes contribute to the advancement of disability-inclusive fashion and aim to enhance the well-being of individuals with disabilities by providing empirical insights into their lived clothing consumption experiences and offering actionable strategies for the development of inclusive fashion products.